2015
DOI: 10.1016/j.jmps.2015.03.011
|View full text |Cite
|
Sign up to set email alerts
|

GPU-based simulations of fracture in idealized brick and mortar composites

Abstract: Stiff ceramic platelets (or bricks) that are aligned and bonded to a second ductile phase with low volume fraction (mortar) are a promising pathway to produce stiff, high-toughness composites.For certain ranges of constituent properties, including those of some synthetic analogues to nacre, one can demonstrate that the deformation is dominated by relative brick motions. This paper describes simulations of fracture that explicitly track the motions of individual rigid bricks in an idealized microstructure; cohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…This model has been studied by a number of authors in much more detail 34,35 and a review of the Young's modulus in staggered brick-and-mortar models can be found in ref. 33.…”
Section: And the References Thereinmentioning
confidence: 99%
“…This model has been studied by a number of authors in much more detail 34,35 and a review of the Young's modulus in staggered brick-and-mortar models can be found in ref. 33.…”
Section: And the References Thereinmentioning
confidence: 99%
“…Most of the modeling studies conducted on nacre-like materials showed that introducing microstructural variations degrades both strength [15] and toughness [16]. Nevertheless, it has been shown that in some configurations, microstructural variations are beneficial.…”
mentioning
confidence: 99%
“…At the micro-scale, we focus our attention on one layer of nacre, which is 300 m thick as previously mentioned. At the most elementary level, many researchers have correlated nacre's microstructure to a brick wall [75][76][77][78][79]. Generally, nacre's microstructure can be grouped into two arrangements, namely columnar and sheet [63].…”
Section: Structure-function Relationships Of Biological Lamellar Strumentioning
confidence: 99%